Acute Myeloid Leukemia in Older Patients: From New Biological Insights to Targeted Therapies - Pasquale Niscola; Valentina Gianfelici; Gianfranco Catalano; Marco Giovannini; Carla Mazzone; Nelida Ines Noguera; Paolo de Fabritiis (Current Oncology)
Acute myeloid leukemia (AML) is a heterogeneous blood-related neoplasm that predominantly afflicts older adults with a poor prognosis due to their physical condition and the presence of medical accompanying comorbidities, adverse biological disease features, and suitability for induction intensive chemotherapy and allogenic stem cells transplantation. Recent research into the molecular and biological factors contributing to disease development and progression has led to significant advancements in treatment approaches for older patients with AML. This review article discusses the latest biological and therapeutic developments that are transforming the management of AML in older adults.